IPT9, a cis-zeatin cytokinin biosynthesis gene, promotes root growth - Antoniadi, Ioanna; Mateo-Bonmatí, Eduardo; Pernisová, Markéta; Brunoni, Federica; Antoniadi, Mariana; Villalonga, Mauricio Garcia-Atance; Ament, Anita; Karády, Michal; Turnbull, Colin; Doležal, Karel; Pěnčík, Aleš; Ljung, Karin; et al. (Frontiers in Plant Science, 2022)
Cytokinin and auxin are plant hormones that coordinate many aspects of plant development. Their interactions in plant underground growth are well established, occurring at the levels of metabolism, signaling, and transport. Unlike many plant hormone classes, cytokinins are represented by more than one active molecule. Multiple mutant lines, blocking specific parts of cytokinin biosynthetic pathways, have enabled research in plants with deficiencies in specific cytokinin-types. While most of these mutants have confirmed the impeding effect of cytokinin on root growth, the ipt29 double mutant instead surprisingly exhibits reduced primary root length compared to wild type. This mutant is impaired in cis-zeatin (cZ) production, a cytokinin-type that had been considered inactive in the past. Here we have further investigated the intriguing ipt29 root phenotype, opposite to known cytokinin functions, and the (bio)activity of cZ. Our data suggest that despite the ipt29 short-root phenotype, cZ application has a negative impact on primary root growth and can activate a cytokinin response in the stele. Grafting experiments revealed that the root phenotype of ipt29 depends mainly on local signaling which does not relate to directly to cytokinin levels. Notably, ipt29 displayed increased auxin levels in the root tissue. Moreover, analyses of the differential contributions of ipt2 and ipt9 to the ipt29 short-root phenotype demonstrated that, despite its deficiency on cZ levels, ipt2 does not show any root phenotype or auxin homeostasis variation while ipt9 mutants were indistinguishable from ipt29. We conclude that IPT9 functions may go beyond cZ biosynthesis, directly or indirectly, implicating effects on auxin homeostasis and therefore influencing plant growth.